The Editorial: Minimum requirements to publish with SJORANM - Frank Mosler; Gerd Nöldge (Swiss Journal of Radiology and Nuclear Medicine)
"Manners maketh man." This phrase is attributed to William of Wykeham (1324–1404) and conveys the idea that good manners and education are essential in shaping a true human being. The expression has also gained wider recognition through the film "Kingsman: The Secret Service".